Is the Association Between TNF-α-308 A Allele and DMT1 Independent of HLA-DRB1, DQB1 Alleles? - Grazyna Deja; Przemyslawa Jarosz-Chobot; Joanna Polanska; Urszula Siekiera; Ewa Malecka-Tendera (Mediators of Inflammation)
The aim of the study was to assess chosen factors of genetic susceptibility to DMT1: DRB1, DQB1, and TNF-α polymorphisms-308 (G/A) in children with DMT1 and their up-to-now healthy siblings. Then we tested whether the association between TNF-α genes and DMT1 is independent of HLA. 87 diabetic children, their 78 siblings, and 85 persons from healthy control group were followed up. The highest risk of DMT1 was connected with alleles: DRB1*0401 (OR = 3.39; CI: 1.55–7.41), DRB1*0301 (OR = 2.72; CI: 1.48–5.01), DQB1*0201 (OR = 4.04; CI: 2.17–7.52), DQB1*0302 (OR = 5.08; CI: 2.54–10.14), and TNF-α-308 A allele (OR = 2.59; CI: 1.23–5.44). Moreover linkage disequilibrium for TNF-α-308 A allele with DRB1*0301 and DQB1*0201 was observed in both diabetic children and their siblings. Diabetic children and their siblings present similar genetic risk factors for DMT1. The association between TNF-α-308 A allele and DMT1 is dependent of HLA-DRB1 and DQB1 alleles.